Implementation of social emotional learning intelligence based self-management - Nanang Kusnendi; Eva Dianawati Wasliman; Deti Rostini (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Vocational education requires students not only to have technical skills, but also good social and emotional abilities to face the world of work. Social-emotional learning based on self-management is one of the approaches implemented in SMKN PP Cilaku and SMKN 1 Cugenang Cianjur Regency to equip students with emotion management skills, communication, and readiness to face professional challenges. This study aims to examine the implementation of social-emotional learning in the two schools and identify the barriers faced in its implementation. The method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and document analysis with principals, teachers, students, and school counselors. The results showed that at SMKN PP Cilaku, experiential learning, mentoring and self-reflection methods helped students to improve their emotional awareness, while at SMKN 1 Cugenang, social simulation and role-playing approaches were emphasized to develop communication and social interaction skills. Although these methods have proven to be effective, there are still obstacles such as teachers' lack of understanding of the concept of social emotional learning, limited school policies, and minimal parental involvement in supporting students' social emotional development. Therefore, increased training for educators, stronger school policy support, and synergy between schools, parents, and industry are needed to optimize the application of social emotional learning in vocational education.This is an open-access article under the CC–BY-SA license.